1973
DOI: 10.1111/j.1365-3059.1973.tb01801.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Yellow Rust and its Control on the Yield of Joss Cambier Winter Wheat

Abstract: SUMMARY Foliar sprays of fungicides were evaluated in a field where winter wheat cv. Joss Cambier was subject to a severe natural infection of yellow rust (Puccinia striiformis Westend.). Almost complete freedom from the disease was achieved on the leaves from repeated applications of BAS 3170F. This material prevented the development of appreciable disease for up to four weeks after spraying. Other chemicals gave varying degrees of protection but most lacked persistence. Control of ear infection was less sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Linear relationships between stripe rust at early milk (GS73) and yield loss were adequate within each year of our study. Such critical point models are consistent with other work (Doling & Doodson, 1968;Mundy, 1973;King, 1976;Brown, 1988;Park et at., 1988;Eskdale, 1991). Our overall regression coefficient was 0 67% yield loss for each 1 % increase in leaf area affected with stripe rust, based on two sites and three years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Linear relationships between stripe rust at early milk (GS73) and yield loss were adequate within each year of our study. Such critical point models are consistent with other work (Doling & Doodson, 1968;Mundy, 1973;King, 1976;Brown, 1988;Park et at., 1988;Eskdale, 1991). Our overall regression coefficient was 0 67% yield loss for each 1 % increase in leaf area affected with stripe rust, based on two sites and three years.…”
Section: Discussionsupporting
confidence: 93%
“…However, critical point models for stripe rust seem to be location dependent. For example, in England, losses of 0-27, 0 44 and 0 39% for each 1% increase in stripe rust at similar stages of crop development were reported by Doling & Doodson (1968), Mundy (1973), and King (1976), respectively. In Australia, Brown (1988) reported 0-48% yield loss per 1% increase in disease in Victoria, Eskdale (1991) reported 0 52",, in northern NSW, andPark et al (1988) reported 0 83% in Queensland.…”
Section: Introductionmentioning
confidence: 91%
“…Percentage losses caused by yellow rust are estimated as being equal to approximately 0-4 times the percentage infection of the flag leaf. This formula is derived from data collected in a single field trial (Mundy, 1973) and in observations made on large numbers of differentially diseased tillers in a commercial crop in 1975 (King, 1976).…”
Section: Estimated Losses In Grain Yield Caused By Diseasesmentioning
confidence: 99%